Smallholders, Market Failures, and Agricultural Production: Evidence from India - Joshua D. Merfeld (Institute of Labor Economics (IZA), 2020)
Market completeness has important implications for household behavior. I firmly reject complete markets for smallholders but am unable to do so for non-smallholders. This leads to important differences in production behavior: smallholders reallocate labor across activities less in response to intra-seasonal crop price changes than do non-smallholders. A counterfactual exercise indicates smallholders could increase revenue by almost nine percent if they were to reallocate labor similarly to non-smallholders. The overall pattern of results is consistent with small-holders lacking sufficient wage employment opportunities. Since non-smallholders have to hire in for agricultural production, this lack of opportunities does not affect their decisions.
Keywords: J20; J43; O13; Q12; Q13; 330; markets; market failures; agriculture; labor